Improving laser welding via decreasing central beam density with a hollow beam. (January 2022) - Li, Quanhong; Luo, Manlelan; Mu, Zhongyan; Huang, Anguo; Pang, Shengyong
Abstract: As it is more and more difficult to achieve good welds by simply adjusting the process parameters and hybrid welding methods in ultra-high power laser welding process, a hollow beam with less central beam density to improve the welding quality is proposed in this paper. The investigation and comparison of predicted keyhole and weld pool dynamics of Gaussian and hollow beam welding on bead-on-plate of 304 stainless steel sheets is initially carried out by numerical simulation. Results show that, compared with Gaussian case, when the hollow beam is used for welding, the amplitude of the keyhole depth is significantly reduced from 2.9 mm to 1.6 mm, and the magnitude of average velocity fluctuations on the weld surface and inside the weld pool are decreased 37.7% and 39.4%, respectively. On the other hand, to verify the possibility of a beam with less central density to improve the welding quality, the welds appearance, process defects and microstructures under Gaussian and hollow beam laser welding are compared and studied by experimental methods. It can be found that for a hollow beam, the spatters and the pores can be effectively suppressed, and the cooling rate during solidification process is increased and the austenite obtained is finer. The grain sizes are about 10 μm in Gaussian case and about 5 μm in hollow case. These studies provide a novel idea for the improvement of laser welding process from the perspective of optimizing the properties of the beam itself, which contribute to change the idea of laser production and laser manufacturing in the future. Highlights: Providing a novel idea for the improvement of laser welding process. Both of the keyhole evolutions and weld pool dynamics are more stable when welding with less central beam density. The less process defects and the finer grains can be obtained by welding with hollow beam.